Analytical investigation of the lineshift and linewidth for the R1 line in YAG: Cr3+ crystals - Koç, H.; Eser, E. (Elsevier B.V., 2019)
In this work, we have investigated the linewidth and shift of R1 line of Y3Al5O12: Cr3+ by using a simple approach in the temperature range of 0–300 K. The results showed a good agreement with the results in the literature. The Debye temperature derived by fit the obtained analytical expression to experimental values in literature. The obtained Debye temperatures of the YAG: Cr vary in the range of 311 K–715 K depending on the experimental data. It was also obtained a single value of the Debye temperatures (?D=574.6K) by using both the lineshifts and linewidths. © 2019
Keywords: Debye functions; The lineshift; The linewidth; Yttrium aluminum garnet